2001
DOI: 10.1177/004051750107100814
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Handle and Sensibility of Woven Silk Fabrics

Abstract: This paper attempts to identify the handle and sensibility of woven silk fabrics for neckties to determine any relationships between them and purchasing preferences. Male and female students evaluate the specimens with a semantic differential scale of handle and sensibility adjectives: twenty-one hand adjectives are grouped as four—“surface sense,” “thermal sense,” “flexibility sense,” and “dryness sense”—and twenty-five sensibility adjectives are grouped as four—“modern,” “classic,” “character,” and “natural”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 5 publications
1
17
0
Order By: Relevance
“…Thus, words should be sampled from all regions of the space, i.e., along all major axes. Additionally, comparison of MDS solutions obtained from data representing perceptions of physical stimuli (in prior studies, Bergmann et al, 2006;Hollins et al, 1993Hollins et al, , 2000Na & Kim, 2001;Picard et al, 2003) versus perceptions of adjectives (in Experiment II) provides a measure of structural similarity between physically-and semantically-based touch spaces.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, words should be sampled from all regions of the space, i.e., along all major axes. Additionally, comparison of MDS solutions obtained from data representing perceptions of physical stimuli (in prior studies, Bergmann et al, 2006;Hollins et al, 1993Hollins et al, , 2000Na & Kim, 2001;Picard et al, 2003) versus perceptions of adjectives (in Experiment II) provides a measure of structural similarity between physically-and semantically-based touch spaces.…”
Section: Resultsmentioning
confidence: 99%
“…Following an approach originated by Yoshida (1968), multidimensional scaling (MDS) techniques revealed that a primary dimension of touch perception is RoughSmoothness (Bergmann Tiest & Kappers, 2006;Hollins, Bensmaïa, Karlof, & Young, 2000;Hollins, Faldowski, Rao, & Young, 1993;Na & Kim, 2001;Picard, Dacremont, Valentin, & Giboreau, 2003). The enduring popularity of roughness as a psychophysical measure is consistent with this finding (Gescheider, Bolanowski, Greenfield, & Brunette, 2005;Klatzky & Lederman, 1999;Lederman, 1974;Lederman & Taylor, 1972;Major, 1895;Ripin & Lazarsfeld, 1937;Smith, Chapman, Deslandes, Langlais, & Thibodeau, 2002).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…The tactile characteristics of solid materials appear well described by three or four orthogonal perceptual dimensions, approximating roughness, softness, elasticity, and slipperiness (Hollins et al 1993(Hollins et al , 2000Na and Kim 2001;Picard et al 2003;Bergmann Tiest and Kappers 2006). In contrast, little is known about the perceptual structure of interactions with fluids, gels, and semisolids.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they noted that these results could be used for the development of better textile fabrics that would satisfy consumers more. Na et al [9] investigated the handle and sensibility of woven silk fabrics used in neckties using the SD technique; they did this in order to determine whether there was a relationship between the handle and sensibility of woven silk fabrics and consumers' purchasing preferences. They made a diagram (distribution map) of the type of silk fabric as a function of the sensibilities, and they concluded that the diagram would be useful when offering basic data for textile design or fabrication to satisfy consumer needs.…”
Section: Introductionmentioning
confidence: 99%